Ground contact time and running speed in Elite Championship distance races - Hunter, I.; Cunningham, R.; Ingebretsen, S.; Butler, D. (34th annual meeting of the American Society of Biomechanics at Brown University Providence, Rhode Island on August 18 - 21, 2010 - Poster 270, 2010)
The goal in distance running is to find a balance between maximum sustainable speed and energy production. This balance plays a vital role in distance running. Throughout the years, athletes have sought for ways to improve performance in this event by balancing the distance of the race with speed. One way to understand the proper balance of distance and speed is to measure running economy at a given speed. Improvements in running economy increase performance in any distance running event. As a runner increases in speed, changes in movement patterns and forces occur. Specifically, the amount of time the runner spends on the ground decreases. Faster athletes are able to apply greater ground forces leading to a shorter ground contact time and greater maximum running speeds . While it is known that as running speed increases, ground contact time decreases, there may also be factors other than speed increases that relate to ground contact time. We hypothesized that ground contact time normalized by speed would be correlated with average running speed during an elite 10 km race on the track. Brigham Young University, Provo, UT Web: http://biomech.byu.edu